Cosmos: astronomy in the new millennium - Pasachoff, Jay M; Filippenko, Alex (Australia, Thomson, 2004)
Jay Pasachoff and Alex Filippenko combine extensive research experience (including years of research in such areas as radio astronomy, solar eclipses, supernovae, active galaxies, black holes and cosmology), teaching experience, and textbook-writing experience to offer a book that presents contemporary science in a way that students can understand. This brief and illustrated text, offers concise coverage of a wide range of astronomical topics. An early discussion of the scientific method stresses its importance in the verification of observations. The authors emphasize the study of origins in this text, first by singling out specifics in the headings of each chapter and then by dealing with a variety of relevant material in the text itself. This edition includes a chapter on the dozens of exoplanets that are being discovered around other stars.
Appendix 1-7, A1-A10p.; Glossary A11-A22p.; Index I1-I11p.
Keywords: Astronomy; Mathematics